Glutamate Transport in Wild-Type and Mutant Strains of Escherichia coli - Halpern, Yeheskel S. (1965)
Halpern, Yeheskel S. (Hebrew University-Hadassah Medical School, Jerusalem, Israel), and Meir Lupo. Glutamate transport in wild-type and mutant strains of Escherichia coli. J. Bacteriol. 90:1288–1295. 1965.—Mutants of Escherichia coli able to grow on glutamate as their source of carbon showed glutamate dehydrogenase and glutamate-oxaloacetate transaminase activities similar to those possessed by the parent strain. The mutants took up glutamate at a much faster rate and showed a several-fold greater capacity for concentrating the amino acid than did the corresponding parent strains. Curvilinear double reciprocal plots of velocity of uptake versus glutamate concentration were obtained with the E. coli H strains. A break in the curve of glutamate uptake was observed with the E. coli K-12 strains when incubated in a glucose medium. It is suggested that these findings may be due to allosteric activation of glutamate permease by its substrate.